Phylogenetic and mutational analysis of H10N3 avian influenza A virus in China: potential threats to human health - Dai, Jingyi; Zhao, Jun; Xia, Jiawei; Zhang, Pei; Ding, Yadi; Li, Qiujing; Hou, Min; Xiong, Xianhui; Jian, Qianqi; Liu, Yanyan; Liu, Guiming (Frontiers in Cellular and Infection Microbiology, 2024)
In recent years, the avian influenza virus has emerged as a significant threat to both human and public health. This study focuses on a patient infected with the H10N3 subtype of avian influenza virus, admitted to the Third People’s Hospital of Kunming City on March 6, 2024. Metagenomic RNA sequencing and polymerase chain reaction (PCR) analysis were conducted on the patient’s sputum, confirming the H10N3 infection. The patient presented severe pneumonia symptoms such as fever, expectoration, chest tightness, shortness of breath, and cough. Phylogenetic analysis of the Haemagglutinin (HA) and neuraminidase (NA) genes of the virus showed that the virus was most closely related to a case of human infection with the H10N3 subtype of avian influenza virus found in Zhejiang Province, China. Analysis of amino acid mutation sites identified four mutations potentially hazardous to human health. Consequently, this underscores the importance of continuous and vigilant monitoring of the dynamics surrounding the H10N3 subtype of avian influenza virus, utilizing advanced genomic surveillance techniques.